PENGENDALIAN MUTU MIKROBIOLOGI ES BATU BERDASARKAN NILAI MOST PROBABLE NUMBER - Marlina, Lusi; Maryam, Irma Nuril; Sarah, Anis (Jurnal TEDC; Vol 20 No 2 (2026): JURNAL TEDCDO - 10.70428/tedc.v20i2.1630, 2026)
The dynamic culinary trends that produce food and beverages utilizing ice cubes as a primary element or sensation enhancer have driven an increase in ice cube consumption, particularly in Bandung. In practice, ice cube production often disregards hygienic factors, posing a risk of contamination by bacteria such as Coliform and Escherichia coli. Therefore, this descriptive laboratory study aims to detect coliform and Escherichia coli bacterial contamination in five samples of consumable ice cubes within the TEDC Polytechnic Bandung environment. Utilizing the Most Probable Number (MPN) method through a series of presumptive, confirmed, and completed tests, it was found that all samples tested positive for coliform, with the highest concentration reaching 240 MPN/100 mL. Furthermore, identification via IMViC tests confirmed the presence of E. coli in one sample. Since the results do not comply with the quality standards set by the Regulation of the Minister of Health (Permenkes) No. 492 of 2010, a rigorous evaluation of hygienity and sanitation in the ice cube production process is required.